Evaluation of Spontaneous DNA Damage Using the Alkaline Comet Assay in Lymphocyte Cells of Humans Living in the High Level Natural Radiation Area of Mamuju, Indonesia: 10.32526/ennrj/20/202100253 - Darlina, Darlina; Kisnanto, Teja; Tetriana, Devita; Purnami, Sofiati; Nugroho Eko Surniyantoro, Harry; Syaifudin, Mukh (Environment and Natural Resources Journal, 2022)
To evaluate the biological impacts of high background radiation exposures that are represented by spontaneous deoxyribonucleic acid (DNA) damage, an evaluation on lymphocyte cells from residents of Mamuju, West Sulawesi, Indonesia was tested. The mean annual dose received by individuals in this area is about 10.40 mSv. Of the 177 adult subjects studied, 102 were from high-level natural radiation areas of Mamuju and 75 subjects were from a nearby normal-level natural radiation area. Both areas are similar in living situations. DNA strand breaks and other parameters of study and control group were determined using a standardized comet assay. Our results showed that chronic low-level natural radiation had resulted in significantly higher (p<0.001) DNA damage based on the three parameters of the assay (tail length, tail DNA, and tail moment) compared to those of control. There was a positive correlation between the level of DNA damage and age, where people aged 40 years and older had a higher level of DNA damage than those under 40 year. The level of DNA damage was also found to be higher in females compared to that of males. It was concluded that chronic exposure to natural radiation in Mamuju had induced spontaneous DNA damage in human cells after long-term exposure which was dependent on age and sex.